2014
DOI: 10.3343/alm.2014.34.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Kiestra Total Laboratory Automation Combined with MS in Clinical Microbiology Practice

Abstract: Background: Microbiological laboratories seek technologically innovative solutions to cope with large numbers of samples and limited personnel and financial resources. One platform that has recently become available is the Kiestra Total Laboratory Automation (TLA) system (BD Kiestra B.V., the Netherlands). This fully automated sample processing system, equipped with digital imaging technology, allows superior detection of microbial growth. Combining this approach with matrix-assisted laser desorption ionizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Mass spectrometry might also become useful in the routine detection of bacterial resistance mechanisms in the future [20]. Additionally, the increasing implementation of total laboratory automation systems offers the opportunity to optimize workflows, reduce costs, and further accelerate microbiological diagnostics [21,22]. On the other hand, external or centralized laboratories may negatively affect the relevance of microbiological data for IC activities, because of delays in result reporting and lack of contact with the hospital problems.…”
Section: Microbiological Supportmentioning
confidence: 99%
“…Mass spectrometry might also become useful in the routine detection of bacterial resistance mechanisms in the future [20]. Additionally, the increasing implementation of total laboratory automation systems offers the opportunity to optimize workflows, reduce costs, and further accelerate microbiological diagnostics [21,22]. On the other hand, external or centralized laboratories may negatively affect the relevance of microbiological data for IC activities, because of delays in result reporting and lack of contact with the hospital problems.…”
Section: Microbiological Supportmentioning
confidence: 99%
“…The first objective is to correctly identify the bacteria to species level, which is now feasible owing to matrix-assisted laser desorption/ionisation time-of-flight (MALDI-TOF) analysis within hours, including identification directly from blood culture bottles [5,6]. Use of MALDI-TOF analysis for identification of bacteria directly from positive blood cultures using automated systems has resulted in a 24-30 h time gain compared with conventional methods [6,7]. It has been demonstrated that early microbial identification by MALDI-TOF even without AST may lead to antimicrobial therapy adjustment in 12% of patients with positive blood culture [7].…”
Section: Introductionmentioning
confidence: 99%
“…Use of MALDI-TOF analysis for identification of bacteria directly from positive blood cultures using automated systems has resulted in a 24-30 h time gain compared with conventional methods [6,7]. It has been demonstrated that early microbial identification by MALDI-TOF even without AST may lead to antimicrobial therapy adjustment in 12% of patients with positive blood culture [7]. The second objective is to decrease the time required for AST of bacteria, which usually requires an additional overnight subculture of the isolated bacterium.…”
Section: Introductionmentioning
confidence: 99%
“…9 The analysis methods used in large-scale microbiology laboratories and institutes are often rigidly configured, 6 making implementation of a totally automated system for HTS a reasonable goal. 10 In contrast, small-and mid-scale laboratories have a growing demand for automated and adaptable laboratory platform technologies that can be applied in partially automated processes. This is because such laboratories lack the capacity and throughput needed to achieve efficient turnaround times when using totally automated laboratory devices.…”
Section: Research-article2015mentioning
confidence: 99%